A typology of board design for highly effective monitoring in intergovernmental organizations under the United Nations system. Issue 2 (2nd September 2018) - Federo, Ryan; Saz‐Carranza, Angel
Abstract: The United Nations (UN) system comprises several intergovernmental organizations (IGOs) that were established to contribute to the functioning of the overall transnational system of delivering global public goods. However, many IGOs under the UN system are criticized for their failure to accomplish their mandates. Research argues that IGO boards serve as a governance mechanism that should be designed in order to effectively perform the monitoring function to ensure fulfillment of IGO mandates. Thus, using an inductive fuzzy set qualitative comparative analysis, this study explores 13 IGO boards under the UN system to identify the board designs that are associated with highly effective monitoring. Our findings reveal a board design typology reflecting the interplay of the level of organizational complexity and the extent of the distribution problem in IGOs. This research contributes to our understanding of IGO governance by underscoring the relationship between board designs and highly effective monitoring to help researchers and practitioners improve IGO performance.